Dynamics of Critical Thinking in Addressing Speaking Skills: A Comprehensive Study Utilizing a Problem-Based Learning Approach - Saputra, Rizky Imam; Rizkiyah, Faiqotur (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this study is to detect the characteristics that enable and hinder the adoption of problem-based learning (PBL) in developing students' speaking abilities through critical thinking. It is expected that by understanding these elements, a successful approach can be formulated to improve educational quality and student outcomes. This study utilizes qualitative research methods along with descriptive techniques. Information was collected through interviews, observation, and analysis of documents. The researchers focused on 27 students in 5th-semester English Education at KH. Mukhtar Syafaat University. As a result, the researchers identified various elements that promote the implementation of PBL aimed at improving students' speaking skills through critical thinking. These factors include available resources and infrastructure, teamwork among group members, and students’ inclination toward solving problems as a group. For hindering factors are time management, prior knowledge, formulating hypotheses, and environment. This environmental factor will affect students' critical thinking and speaking skills. And it is the main factor why most of the 5th semester TBIG students are still lacking in critical thinking.